Patterns and Outcomes of Nodular Thyroid Disease in Benghazi, Libya - Miftah, Tawfeeq A.; Buzaid, Najat O.; Lawgaly, Sami A.; Twati, Mussa G.; Albash, Amina M. (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
Most studies on thyroid nodules in Libya have been conducted on histopathological samples. This study was conducted on patients attending endocrine clinics in Benghazi, Libya.This article aims to describe the clinical, radiological, biochemical, and pathological aspects and outcome of nodular thyroid disease in Benghazi, Libya.A total of 227 patients with nodular thyroid disease who attended the endocrine clinics of Benghazi Medical Center and 7th October Hospital during the year 2023 were included in the study. Records were reviewed regarding age, sex, clinical presentation, history of previous head and neck radiotherapy, number and size of nodules, presence and site of lymphadenopathy, thyroid ultrasound features, thyroid-stimulating hormone (TSH), fine-needle aspiration cytology (FNAC) results, outcome (surgery and its type or follow-up), results of histopathology, and final diagnosis.Most of the studied group was females, 213 (93.8%). The mean age ± standard deviation (SD) was 52.3 ± 13.5 years. Multinodular goiter represented the highest percentage and accounted for 142 (62.6%). Mean nodule size ± SD was 2.4 ± 1.5 cm, and the median TSH level was 1.7 mIu/L. Regarding FNAC, most of the cases (110, 44.1%) were benign/colloid goiter, follicular neoplasm, or malignant (19, 8.3%). Among the 54 patients who had a histopathological diagnosis, 26 (48.1%) were proven to have thyroid carcinoma, and most of them had papillary carcinoma (24/26, 92.3%). Among 28 benign cases, 13 (24.5%) had Hashimoto's thyroiditis.Nodular thyroid disease was more common in females; most cases had multiple nodules. FNAC was benign colloid in more than half of the cases, and malignancy or suspicious for malignancy was found in 10% of the cases. Half of the cases with histopathological diagnosis had thyroid carcinoma, and most of them were papillary thyroid carcinoma.
Keywords: nodules; thyroid; nodular; TIRADS; fine-needle aspiration cytology; Benghazi; Libya